Analysis of morphological differences between prehistoric populations using a non-hierarchic method of data clustering - Sołtysiak, Arkadiusz; Jaskulski, Piotr (Polskie Towarzystwo Antropologiczne, 1999)
Presented in this paper non-hierarchic method of cluster analysis allows studying of morphological variability in big populations on the basis of individual characteristic of specimens. Test taken by the authors have confirmed correct results of the proposed algorithm and showed the role of proper preparation of data, choice of appropriate distance measure and importance of the process of interpretation the results of clustering.